Effect of osmotic dehydration of olives as pre-fermentation treatment and partial substitution of sodium chloride by monosodium glutamate in the fermentation profile of Kalamata natural black olives. (May 2017) - Bonatsou, Stamatoula; Iliopoulos, Vasilis; Mallouchos, Athanasios; Gogou, Eleni; Oikonomopoulou, Vasiliki; Krokida, Magdalini; Taoukis, Petros; Panagou, Efstathios Z.
Abstract: This study examined the effect of osmotic dehydration of Kalamata natural black olives as pre-fermentation treatment in combination with partial substitution of NaCl by monosodium glutamate (MSG) on the fermentation profile of olives. Osmotic dehydration was undertaken by immersing the olives in 70% (w/w) glucose syrup overnight at room temperature. Further on, three different mixtures of NaCl and MSG with/without prior osmotic dehydration of olives were investigated, namely (i) 6.65% NaCl – 0.35% MSG (5% substitution), (ii) 6.30% NaCl – 0.70% MSG (10% substitution), (iii) 5.95% NaCl – 1.05% MSG (15% substitution), and (iv) 7% NaCl without osmotic dehydration (control treatment). Changes in the microbial association (lactic acid bacteria [LAB], yeasts, Enterobacteriaceae ), pH, titratable acidity, organic acids, sugars, and volatile compounds in the brine were analyzed for a period of 4 months. The final product was subjected to sensory analysis and the content of MSG in olives was determined. Results demonstrated that osmotic dehydration of olives prior to brining led to vigorous lactic acid processes as indicated by the obtained values of pH (3.7–4.1) and acidity (0.7–0.8%) regardless of the amount of MSG used. However, in non-osmotically dehydrated olives, the highest substitution level of MSG resulted in a final pH (4.5) that was beyond specification for this type of olives. MSG was degraded in the brines being almost completely converted to γ-aminobutyric acid (GABA) at the end of fermentation. Finally, the sensory assessment of fermented olives with/without osmotic dehydration and at all levels of MSG did not show any deviation compared to the control treatment. Highlights: The effect of osmotic dehydration of olives and use of MSG in the brine was investigated. Osmotic dehydration of olives resulted in vigorous fermentation based on pH and acidity. The use of glucose as osmotic solute enriched the brine with fermentable material. High levels of MSG in the brines resulted in high combined acidity values. MSG was almost completely converted to GABA at the end of fermentation.